The Epistle of Salim ibn Dhakwān - Sālim ibn Dhakwān, active 8th century; Crone, Patricia, 1945-2015.; Zimmermann, Fritz (Fritz W.) (Oxford ; New York : Oxford University Press, 2001)
The epistle ascribed to Salim Ibn Dhakwan, and written sometime before AD 800, was discovered in the early 1970s by the scholar, Amr Khalifa Ennami, who brought a xerox of the now lost manuscript to the attention of Islamic scholars. The epistle which is here edited, translated, and discussed in full for the first time is an early Islamic tract against `wrong' doctrines regarding the classification and treatment of opponents.
Intro; Title Page; Preface; Contents; A Note on Conventions; Part 1; 1. Introduction; Signs and Abbreviations; 2. The Epistle of Salim B. Dhakwan; 3. Commentary; Part 2. Salim, the Mainstream, and the Ibadi Tradition; 4. 'Uthman and 'Ali; 5. The Kharijites; 6. The Murji'a and Fatana; 7. Salim and Kitab Al-Irja'; Part 3; 8. The Date of Salim's Epistle; Appendix 1: The Ibadi Leaders in Basra; Appendix 2: The Imams of Oman till 280/893; Appendix 3: Ma/man/haythu sha'a 'llah; Appendix 4: Isti'rad; Appendix 5: Al-murji'a al-ula in the radd 'ala ahl al-shakk; Bibliography; Index to the Arabic Text
Arabic epistle which is here edited, translated, and discussed in full for the first time.
Includes bibliographical references (pages 333-357) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Sālim ibn Dhakwān, -- active 8th century; Sīrat Sālim ibn Dhakwān (Sālim ibn Dhakwān); Ibadites; Kharijites; Murjiʼah; Islam -- Doctrines; Shīʻah -- Doctrines; Ibāḍites.; Khārijites.; Murjiʻah; Islam -- Doctrines; Chiisme -- Doctrines; RELIGION -- Islam -- General; Ibadites; Islam -- Doctrines; Kharijites; Murjiʼah; Shīʻah -- Doctrines